PENGARUH ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP DAYA SAING DAN KINERJA PEMASARAN - Maylista, Sylvia; Wijayanto, Gatot; Henni Noviasari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the effect of Market Orientation and Product Innovation on Competitiveness and Marketing Performance of Culinary MSMEs in Pekanbaru City. The population in this study is MSMEs that have Micro Small Business Permits (IUMK), which are 331 MSMEs, and the sample used in this study is 181 MSMEs using the slovin formula. Data collection was carried out through distributing questionnaires to Culinary MSME owners in Pekanbaru City. The analytical technique used in this study is path analysis with the help of SPSS to see the effect of the dependent variable on the independent variable. The results showed that market orientation and product innovation had a positive and significant effect on competitiveness. Market Orientation, Product Innovation and Competitiveness have a positive and significant impact on Marketing Performance. And Competitiveness positively and significantly mediates the effect of Market Orientation and Product Innovation on Marketing Performance on Culinary MSMEs in Pekanbaru City.